Pendampingan Persiapan Psikologis Pranikah pada Calon Pasangan Pengantin Muslim melalui Kursus Calon Pengantin (Suscatin) Berbasis Komunitas di Kelurahan Jambangan Kota Surabaya - Triana Rosalina Noor; Wenika Agustitia (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
Individual wishing a happy marriage, this can be achieved with effort and hard work. One effort that can be done to achieve a happy marriage is to have the right information about married life, thereby can bring up individual awareness that not always marriage is happy, and not always marriage always faces problems. The existence of premarital knowledge will make the individual has readiness in the face of the dynamics of marriage, more able to accept the reality of marriage life and can improve the quality of marriage. This dedication was held in January-March 2017. As for prenuptial psychological counseling process was done by preparing the module book containing the material related to the marriage life that would be discussed and discussed in the mentoring process in the guidance counseling session. The location of the research took place at RW 1 Keluahan. Jambangan Surabaya. These mentoring groups were five prospective Muslim couples who would be married within a period of <6 months and between 6-12 months. The result of this mentoring was that the preparation of prenuptial psychological preparation for Muslim couples was one of the right ways to help the stability of prospective couples before marriage. Through the mentoring that used of module books and counseling process, could facilitate the prospective couples in opening insights about the marriage life, so that it could formulate how the family settings they would build.